The Importance of Context Theory in Language Education - F. Ben Amer, Salwa (مجلة كلية الاداب, 2024)
In common use, almost every word has many shades of meaning, therefore, it needs to be interpreted by context. A context theory is a very important theory in language education. This paper aims to show the notion of context and its importance in communication and language study which has been extensively studied by different linguists from different perspectives. Moreover, in today's world, there is a growing need to learn how to use language appropriately in context and it is widely accepted that language requires context in order to function as a medium of communication between speakers and listeners. Therefore, effective communicator needs to understand all forms of context to master all forms of verbal and physical exchanges of information and as listeners, they make use of background knowledge about the speaker, concepts and previous utterances in order to infer the speaker's intended meaning. Therefore, effective language teachers treat language as a whole integrated communication system and use it as a context to facilitate their students learning. In this paper, the author emphasizes the importance of context theory in interactive language teaching concentrating on developing natural language communication and the teacher aims to use all language activities in meaningful situation and how to promote the students' communicative competence in the context and use all knowledge about language in meaningful situation to negotiate meaning and get their message through.